Adopting a Wider Approach for Fisheries Management - Anthony, Donald Hawkins (International Marine Science Journal, 2022)
Many marine and freshwater fisheries are now in a very poor state, and many fish stocks are close to collapse. There is a need to manage fisheries more carefully, especially since fishing can affect other aspects of the environment. It is also important to reduce the adverse effects of climate changes upon the marine and freshwater environments, fishes, and other animals, and the need to manage other human activities taking place in the sea, to improve the marine environment and protect the wildlife and the fishing activities. Marine pollution, includes human waste materials, chemicals and plastics, and there is also noise and substrate vibration, from industrial and other activities that may affect both the abundance and quality of fishes and other marine animals. This paper deals with fisheries management, and environmental protection, and concludes that fishermen, fisheries scientists, fisheries managers and environmental interests must work closely together, if fishes are to be adequately protected, and fisheries are to be better managed. It describes current systems of management. It especially draws attention to the importance of moving towards an ecosystem-based approach to fisheries management. Such an approach aims to manage all those human activities that have an impact upon the marine environment and its life forms.
Keywords: Fishes; Fisheries; Environments; Ecosystems; Management. Scientists.